2001
DOI: 10.1051/0004-6361:20011490
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of recently discovered planetary nebulae towards the galactic bulge

Abstract: Abstract. In this work we report spectrophotometric observations of a planetary nebula sample towards the galactic bulge. A total of 45 PNe was observed and their physical parameters (electron density and temperature) were derived. Ionic abundances were calculated using a three-level atom model and abundances were derived through ionisation correction factors. Results show low abundance objects at high galactic latitudes, indicating a possible vertical gradient inside the bulge. A few objects with low N/O rati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 27 publications
7
63
1
Order By: Relevance
“…They also had to contain enough objects to allow us to assess their quality and internal integrity in a way that is similar to our own data presented here. These requirements were met by the following papers: de Freitas Pacheco et al (1992), Kingsburgh & Barlow (1994), Cuisinier et al (1996Cuisinier et al ( , 2000, Ratag et al (1997), Escudero & Costa (2001), Kwitter & Henry (2001), Peña et al (2001), Milingo et al (2002), Escudero et al (2004), Exter et al (2004), Górny et al (2004Górny et al ( , 2009, Girard et al (2007), Wang & Liu (2007), Cavichia et al (2010), Henry et al (2010), and Górny (2014). In short, we found useful optical spectroscopic literature data for 76, 30, and nine Galactic PNe in the lists by Stanghellini et al (2012), Perea-Calderón et al (2009), andGutenkunst et al (2008), respectively.…”
Section: Nebular Abundances From Literature Datamentioning
confidence: 99%
“…They also had to contain enough objects to allow us to assess their quality and internal integrity in a way that is similar to our own data presented here. These requirements were met by the following papers: de Freitas Pacheco et al (1992), Kingsburgh & Barlow (1994), Cuisinier et al (1996Cuisinier et al ( , 2000, Ratag et al (1997), Escudero & Costa (2001), Kwitter & Henry (2001), Peña et al (2001), Milingo et al (2002), Escudero et al (2004), Exter et al (2004), Górny et al (2004Górny et al ( , 2009, Girard et al (2007), Wang & Liu (2007), Cavichia et al (2010), Henry et al (2010), and Górny (2014). In short, we found useful optical spectroscopic literature data for 76, 30, and nine Galactic PNe in the lists by Stanghellini et al (2012), Perea-Calderón et al (2009), andGutenkunst et al (2008), respectively.…”
Section: Nebular Abundances From Literature Datamentioning
confidence: 99%
“…The data set for 164 PNe from Górny et al (2004) come from the merging of data for 44 PNe observed by Górny in 2000 with those for PNe observed by Cuisinier et al (2000), Escudero & Costa (2001), and Escudero et al (2004). In this way, we obtain the largest sample of PNe with high-quality data observed in the direction of the Galactic bulge (for a detailed description, see Górny et al 2009), with 245 objects (for the 39 objects belonging to more than one sample, the best data were chosen).…”
Section: Bulge and Inner-diskmentioning
confidence: 99%
“…This number is low compared with the estimated numbers of ∼ 2000 GBPNe by Gesicki et al (2014) and ∼ 3500 GBPNe by Peyaud et al (2006). The currently number of GBPNe with accurate chemical abundances is ∼ 300, considering the works done by Escudero & Costa (2001); Escudero et al (2004); Cavichia et al (2010), hereafter IAG-USP sample, and also the works of Górny et al (2009), Wang & Liu (2007), Cuisinier et al (2000), Exter et al (2004), as compiled by Chiappini et al (2009). The fact that PNe are originated from stars of different masses and, consequently, evolutionary pathways, hamper the construction of representatives samples for unbiased chemical composition studies.…”
Section: Introductionmentioning
confidence: 77%